A novel circRNA, circRACGAP1, hampers the progression of systemic lupus erythematosus via miR-22-3p-mediated AKT signalling. (18th August 2022) - Mei, Han-Ying; Liu, Ju; Shen, Xiao-Ping; Wu, Rui
Abstract: Background: Systemic lupus erythematosus (SLE) is defined as a multisystem autoimmune disease involving various organs, of which exact molecular mechanisms remain elusive. Here, we aimed to investigate a novel circular RNA (circRNA), circRACGAP1, abnormally expressed in SLE and explored its underlying regulatory network. Methods: The expression patterns of circRACGAP1 were determined in patients diagnosed with SLE by using a qRT-PCR assay. Spearman correlation analysis was employed to evaluate the correlation between circRACGAP1 and clinicopathological variables in patients with SLE. Flow cytometry and TUNEL assays were subjected to assess the cell apoptosis. Nuclear-cytoplasmic fractionation and luciferase reporter assay was used to verify the circRACGAP1/miR-22-3p/PTEN axis. Western blot analysis was performed to measure the PTEN/AKT signalling-related proteins and apoptotic-related biomarkers. Results: Down-regulated circRACGAP1 was observed and correlated with Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score, anti-double-stranded (ds) DNA, and complement C3 level in patients with SLE. Overexpression of circRACGAP1 significantly alleviated cell apoptosis in Jurkat cells within UVB exposure. Mechanistic investigation revealed that circRACGAP1 could serve as a sponge of miR-22-3p to regulate PTEN/AKT signalling. Conclusions: Collectively, circRACGAP1 regulated the AKT signalling pathway via binding to miR-22-3p in the progression of SLE, suggesting therapeutic targets for SLE treatment.